(untitled) (International Journal of Engineering and Computer Science, 2017)
IPV4 and IPV6 are incompatible protocol that means one device with IPV4 address cannot directly communicate with the IPV6 address. Many network devices are IPV4-only, they will not communicate in IPV6-only environment and few of those can or will upgrade to IPV6. The purpose of this study is to configure the network with address allocation, router configuration with OSPF routing protocol, implementation of Dual-stack, tunnels namely Manual Tunnel, GRE-IPv4 tunnel, ISATAP and 6to4 tunnel, it allows the communication between the IPv4 and IPv6 network hosts. The entire configuration is implemented using GNS3 simulator.